(3efThQ Edi LeGYI CHj fRhGH TjhN GdehVhYs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3ef GdCgd hGdCUMGH HSe Gddg GdQMef GdQMje CWGd Gddg HbGA ENhGfi GdTjhN GdWgQI hMSf fjGJge hJajbge hChVM Edi GdeYGdi Hejehf JeGe GdWGYI s
(3BNQgG (B:s
(3Ydi CMSf eG JbOe ef GaYGdg dce jchf gPG GdcJGH ebQhAkG ai jO GdTjN CHj GdTHd hGdMeO ddg hMOg hgh MSHi hfYe GdfUjQ GdeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B95s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis